Integrating machine learning and empirical approaches for scour depth estimation at sluice gates: evaluating tree-based models, hyperparameter tuning, and proposing new formulas - Le Xuan-Hien; Hien Le Thi Thu (Journal of Hydrology and Hydromechanics)
Abstract: